PEMBUATAN MINUMAN HERBAL JAHE SERBUK DAN NATA LIDAH BUAYA DARI TANAMAN OBAT KELUARGA (TOGA) DI NAGARI SIKUCUR KECAMATAN V KOTO KAMPUNG DALAM KABUPATEN PADANG PARIAMAN - Dira Hefni; Netty Suharti; Yoneta Srangenge (Jurnal Hilirisasi IPTEKS, 2022)
TOGA (Family Medicinal Plant) is a type of plant that is cultivated around the yard or yard of thehouse and has a function as a medicinal plant. TOGA can be used to reduce the use of modern medicineswhich tend to be expensive and have many side effects. The existence of TOGA in the home environmentis very important. The use of TOGA in self-medication provides a cheap, fast, and convenient solution inovercoming minor ailments. Counseling and education to the public regarding the use of TOGA plantsare expected to encourage people to "back to nature", as well as optimize the role of plants around themas TOGA in self-medication efforts. Communities in Nagari Sikucur Kampung Dalam Padang Pariamangenerally have land that has been planted with TOGA but its utilization is still not optimal due to lack ofknowledge, education, and socialization to the community. The purpose of this activity is to provideunderstanding and knowledge to the public regarding the use, processing, and utilization of TOGA as anherbal drink that is beneficial for health properly and properly. This activity was carried out in two stages,namely 1) Counseling on the use of Family Medicinal Plants (TOGA) as herbal drinks 2) Demonstrationof processing TOGA into herbal drinks. The result of this activity is that women in Nagari SikucurKampung Dalam Padang Pariaman get information and knowledge about the benefits and processing ofTOGA into herbal drinks in the form of powders and fresh drinks.